Long term renal recovery in survivors after OHCA. (August 2019) - Jamme, Matthieu; Ait Hamou, Zakaria; Ben Hadj Salem, Omar; Guillemet, Lucie; Bougouin, Wulfran; Pène, Frédéric; Cariou, Alain; Geri, Guillaume
Abstract: Backgrounds: In survivors of out-of-hospital cardiac arrest (OHCA), acute kidney injury (AKI) is frequent and is associated with numerous factors of definitive renal injury. We made the hypothesis that AKI after OHCA was a strong risk factor of long-term chronic kidney disease (CKD). We aimed to evaluate long-term renal outcome of OHCA survivors according the occurrence of AKI in ICU. Methods: We used prospectively collected data from consecutive OHCA patients admitted between 2007 and 2012 in a tertiary medical ICU. AKI was defined by the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Long-term creatinine level was the last blood creatinine assessment we were able to retrieve. The main outcome was the occurrence of CKD, defined by an estimated glomerular filtration rate (eGFR) lower than 60 mL/min/1.73m 2 according to the MDRD equation. Long-term mortality was evaluated as well. Factors associated with CKD occurrence were evaluated by competing risk survival analysis (Fine Gray and Cox cause specific models). Results: Among the 246 OHCA patients who were discharged alive, outcome of 133 patients was available (median age 55 [iqr 46, 68], 75.2% of male). During a median follow-up time of 1.8 [0.8–2.5] years, CKD occurred in 17 (12.7%) patients and 24 (18%) patients died. A previous history of arterial hypertension (sHR = 3.28[1.15;9.39], p = 0.027; CSH = 4.83 [1.57;14.9], p = 0.006), AKI during ICU stay (sHR = 3.72[1.40;9.84], p = 0.008; CSH = 5.41[1.79;16.3], p = 0.003) and an age higher than 55 (sHR = 6.13[1.55;24.3], p = 0.009; CSH = 2.16[1.72;43.8], p = 0.006) were independently associated with CKD occurrence. AKI was not associated with long-term mortality (sHR = 0.73 [0.27;1.99], p = 0.55; CSH = 0.75 [0.28;2.01], p = 0.57). Conclusion: In OHCA survivors, CKD was a frequent long-term complication. AKI during ICU stay was a strong determinant of long-term CKD occurrence.